Conservation Priority Land Selection in Sangiran Mountainous Dome Area using Remote Sensing Data - Sulistyo, Bambang (Forum Geografi, 1996)
The purpose of this study is to describe the features of soil forms on PKS derived from the data which are related to the erosions that happen. Based on this, the location of the priority of the soil conservation can be chosen. The research geomorphologic hazard method applied in this study is the continuation of the previous research which has yielded the study of soil form area. The result of that study is combined to other data to know IBE which covers topography, slope area, the count, it can be determined the priority of the soil conservation based on the delineation of the soil forms which are interpreted from remote sensing data especially the aerial photograph. The conclusion are 1) the choice of the priority of soil conservation and cultivating plants an be done by knowing IBE; 2) the degree of priority of the soil conservation and plant cultivation in PKS depend on the spreads of the soil forms. The soil forms happened is the features of the difference of rock formations, litology, the degree of erosion, landslide, and the process of diafirism. The priority sequences of the loations of the soil conservation and plant cultivation are S3 dan S4 followed by S5, s1, S2, and finally F1.